FRI0582 Fluctuating Levels of Rheumatoid Factor Predict Progression of Rheumatoid Arthritis, but Not Independent of Disease Activity. (15th July 2016) - Unger, M.; Alasti, F.; Supp, G.; Studenic, P.; Smolen, J.; Aletaha, D.
Abstract : Background: The presence of rheumatoid factor (RF) is associated with progression of joint damage in patients with rheumatoid arthritis (RA). RF levels may change during the course of therapy 1, but it is not clear, if such changes also reflect a change in prognosis of RA. Objectives: Here, we aimed to investigate whether fluctuation of RF levels is an independent marker of progression of RA. Methods: We identified 239 RA outpatients based on classifiable RA by the 2010 ACR/EULAR classification criteria, the presence of at least two available radiographs of hands and feet (2–4 years apart), the availability of repeated measurements of RF (at least two/year), and positive initial RF levels (≥50 IU/ml; for the possibility of fluctuation). Radiographic images were scored using the modified Sharp/van der Heijde (SvH) method. A total of 375 radiographic intervals could be included, since some of the patients had more than one included observation periods. Logistic regression analysis was used to examine the effect of fluctuating RF levels (expressed as standard deviation of all RF measurements between the two radiographs) on significant damage progression (defined by an average increase of ≥3 on the SvH score per year); results were adjusted for mean RF levels over time, disease activity (expressed as Simplified Disease Activity Index – SDAI), percentage time on biologics and already existing radiographic damage. Results: Mean (SD) RF levels were 351.4 (618.7) IU/ml at baseline and 253.7 (424.2) IU/ml at the time of the second radiograph (p<0.001). Mean and standard deviation of RF levels within each patient were on average 298.9 (515.0) and 128.7 (233.8), respectively. Mean time-integrated levels of disease activity (SDAI) were of 9.7 (7.0), and patients received biologic therapy over 32.4 (40.8) % of the observed time. Pre-existing damage was 41.1 (52.4) points on the SvH score. Univariate logistic regression showed a clear association of higher standard deviations of RF levels with radiographic progression (p=0.015). When adjusting this effect for mean RF levels, disease activity (time-integrated levels of SDAI), percentage time on biologics and already existing radiographic damage, the association of standard deviation of RF levels on radiographic progression was lost (p=0.087), whereas disease activity (p<0.001) and pre-existing damage (p=0.001) showed high significance. When adjusting for each of these predictors individually, the association remained unchanged when tested against time on biologics only (p=0.016), or pre-existing damage only (p=0.048). Even adjusting for mean RF levels only left a significant independent association (p=0.032), while the mean RF levels were not significant (p=0.146). Only when adjusted for time-integrated disease activity, standard deviation of RF lost significance on the association with radiographic progression (p=0.126; Table ). Conclusions: Fluctuations of RF levels are associated with radiographic progression in RA. This effect is independent of mean RF levels over time, but seems to be associated with, or a consequence of, disease activity. Further studies need to explore the direction of causality of these observations. References: Serological changes in the course of traditional and biological disease modifying therapy of rheumatoid arthritis. Böhler C et al. Ann Rheum Dis, 2013 Feb;72(2):241–4. Disclosure of Interest: None declared